How Carbon Source and Degree of Oligosaccharide Polymerization Affect Production of Cellulase-Degrading Enzymes by Fusarium oxysporum f. sp. lycopersici - Najjarzadeh, Nasim; Matsakas, Leonidas; Rova, Ulrika; Christakopoulos, Paul (Frontiers in Microbiology, 2021)
Cellulases are a group of enzymes responsible for the degradation of cellulose, which is one of the most abundant polymers on Earth. The three main groups of cellulases are endoglucosidases, exoglucosidases, and β-glucosidases; however, the mechanism of induction of these enzymes remains poorly characterized. Cellooligosaccharides are among the main inducers of these enzymes in filamentous fungi, yet it is not clear how their degree of polymerization may affect the strength of induction. In the present study, we investigated the effect of different carbohydrate-based inducers, such as lactose, sophorose, cellooligosaccharides, and xylooligosacharides, characterized by different concentrations and degree of polymerization, on cellulases production by the fungus Fusarium oxysporum f. sp. lycopersici, which is one of the most studied lignocellulose degrading fungi with the ability to consume both cellulose and hemicellulose. Moreover, the effect of carbon source on cellulase induction was assessed by growing the biomass on sucrose or glycerol. Results showed a correlation between induction efficiency and the cellooligosaccharides’ concentration and size, as well as the carbon source available. Specifically, cellotetraose was a better inducer when sucrose was the carbon source, while cellobiose yielded a better result on glycerol. These findings can help optimize industrial cellulase production.